Enhancing Public Participation in The Process of Sorting Household Waste from the Source from the Housewives Point of View - بنون خيرالدين; العينوس رياض (Finance and Business Economies Review, 2021)
This papers attempted to address the problem of enhancing public participation in sorting household waste at the source from the point of view of housewives. We use a survey based method for a sample of household. We found that there is great wiling from housewives to participate in sorting household waste if it was adopted by the authorized authority. Also, We also found that the factors of law and social norm are more important statistically than the factors of financial motivation, and just as important as knowledge and know-how factors as factors to enhance the contribution of housewives in the strategy of sorting waste from the source, noting that all of these factors are important, but with a slight variation in importance.